SISTEM PERTANIAN TERPADU TANAMAN PADI DAN BEBEK PETELUR - Muhamad Suproni; Dedy Suheimi (Jurnal Kommunity Online, 2022)
ABSTRACTThe integrated farming system is an effort to take advantage of the linkages between food crops, horticulture, plantations with livestock and fisheries. One of the activities carried out by the Benteng Mikro Indonesia Sharia Cooperative is through member empowerment activities, namely rice cultivation and duck farming. Rice cultivation activities carried out on an area of 10 hectares. The yield obtained during the cultivation period was 32 tons, of the 32 tons of GKP produced as many as 27 tons of GKG. Laying duck feed is obtained from the bran produced from the grain milling process using a micro-scale milling machine. The micro-scale machine used has a capacity of 1 ton per hour to produce rice into rice, with the production of 1 ton of milled dry grain can produce 30-40% bran. The bran is used by farmers to feed laying ducks, the aim is to minimize production costs, especially feed costs. The need for bran in 100 ducks per day is 15 kg to 20 kg, so the costs incurred are Rp. 30.000/day for feed. Other feed is in the form of snails which are also obtained from rice fields cultivated by farmers. The income of duck egg farmers is Rp. 78,000,00. If it is assumed for 30 days then per month the income received by the farmer is Rp. 2,340,000,00. The role of the integrated farming system in the Indonesian Benteng Mikro Syariah Cooperative in empowering members of farmers or breeders through production cost efficiency and increasing daily income by combining rice cultivation and laying ducks..Keywords: paddy, duck